2014
DOI: 10.1017/s1041610214001112
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in centenarians: the international landscape

Abstract: Suicide rates were sufficiently large amongst centenarians for there to constitute a public health concern given the anticipated rise in the centenarian population and the paucity of data on risk and protective factors for suicide in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…A previous study found that suicide rates slightly increased again in the 100 years age band. 42 Due to the low number of centenarians in our study, we could not investigate the risk of suicidal behaviours in this age group.…”
Section: Discussionmentioning
confidence: 93%
“…A previous study found that suicide rates slightly increased again in the 100 years age band. 42 Due to the low number of centenarians in our study, we could not investigate the risk of suicidal behaviours in this age group.…”
Section: Discussionmentioning
confidence: 93%
“…Although suicide rates increase steadily with age in most regions of the world, with rates continuing to increase also in the older age groups (Shah et al, 2014), suicide in older adults is still a relatively neglected topic in suicide research and there is lack of suicide prevention activities in older adults (Lapierre et al, 2011). Nevertheless, the average annual rate of suicides for older adults in Queensland was lower compared to middle-aged adults: 15.27 per 100,000 persons and 18.77, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these considerations, what is being observed is that suicide rates continue to be the highest in late life, particularly among males. For example, a study conducted by Shah and associates [10] showed that suicide rates continue to increase in centenarians too. A remarkable phenomenon is represented by the progressive widening of the disproportion between suicide rates of males and those of females, with males of very advanced age expressing rates of suicide up to 7-8 times bigger than those of old-old females [10] (in younger age groups of western countries the suicide rate ratio between males and females is approximately three to one).…”
Section: 'Limits' Of Old Age and Suicide Data Limitsmentioning
confidence: 99%